Corporate governance in South Korean laws: Some suggestions for Vietnam - Phan, Thi Thanh Thuy (H. : ĐHQGHN, 2020)
Having an advanced legal framework for corporate governance is always one of the most prerequisites for effective business operation of joint stock companies. Being aware of this issue, since the first enactment in 1990, enterprise law in Vietnam has been consecutively improved and newly promulgated to absorb the OECD modern principles of corporate governance and good international practices, particularly from the developed countries which have successful economic cooperation with Vietnam in Asia. This article will focus on exploring and analyzing and making comments on the legal framework and corporate structures of joint stock company regulated in Korean Commercial Code. In term of comparison with those similar elements in Vietnamese Enterprise Law 2014, the article will also make recommendations as suggestions for the improvement of corporate governance law in the country.